1996
DOI: 10.1021/jp951577j
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Diffusion Coefficients in Two-Dimensional Fluid Media Measured by the Pyrene Excimer Reaction

Abstract: Diffusion-controlled bimolecular reactions in two-dimensional or quasi two-dimensional space are important in both surface and membrane reaction kinetics. A model reaction that has been extensively used to study the dynamics and structure of phospholipid membranes is the formation of the excimer of pyrene. We present experimental evidence that in multilamellar liposomes of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine, in the fluid phase at temperatures above phase transition, T L , and for a probe/phosphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
43
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 34 publications
7
43
0
Order By: Relevance
“…However, although in 3D the rate coefficient tends asymptotically to a constant value, the rate coefficient in 2D tends to zero at long times. The formalism for 2D diffusion-controlled kinetics was introduced by Razi Naqvi (1974), and we have proved that, in the case of 1-palmitoyl-2-(1-pyrenedecanoyl)-sn-glycero-3-phosphocholine (py 10 -PC) in fluid 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayers, this formalism conduces to a selfconsistent kinetic analysis of pyrene monomer and excimer fluorescence (Martins et al, 1996). Moreover, we have also shown that, whatever the time range considered, and for a large range of diffusion coefficients, encounter distances, and 2D concentrations, Razi Naqvi's formalism is in perfect accordance with the results of the simulation of 2D bimo-lecular reactions using Monte Carlo techniques (Martins et al, 2000).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, although in 3D the rate coefficient tends asymptotically to a constant value, the rate coefficient in 2D tends to zero at long times. The formalism for 2D diffusion-controlled kinetics was introduced by Razi Naqvi (1974), and we have proved that, in the case of 1-palmitoyl-2-(1-pyrenedecanoyl)-sn-glycero-3-phosphocholine (py 10 -PC) in fluid 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayers, this formalism conduces to a selfconsistent kinetic analysis of pyrene monomer and excimer fluorescence (Martins et al, 1996). Moreover, we have also shown that, whatever the time range considered, and for a large range of diffusion coefficients, encounter distances, and 2D concentrations, Razi Naqvi's formalism is in perfect accordance with the results of the simulation of 2D bimo-lecular reactions using Monte Carlo techniques (Martins et al, 2000).…”
Section: Introductionmentioning
confidence: 90%
“…If so, this should imply that the effective 2D quencher concentration is doubled with respect to the case where the reaction takes place independently in each leaflet. We have proved in a previous work (Martins et al, 1996) that in fluid bilayers of POPC the pyrene moiety of probes pertaining to different sides can in fact interact, because only on this condition the parameters retrieved, namely M , from the analysis with the 2D formalism have physical meaning. This is apparently inconsistent with the value of 1.11 nm for the depth of the effective center of the pyrenyl moiety of py 10 -PC measured from the bilayer/water interface in POPC bilayers quoted by Sassaroli et al (1995).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Different experimental techniques are widely used for the determination of the bulk and surface diffusion coefficients (5)(6)(7)(8). An original simple idea for the simultaneous measurement of both diffusion coefficients is discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%